Estimation of Charge Carrier Density of Turmeric Dye in the Presence of Polyvinyl Alcohol (PVA) and Its Electrical Characterization as Herbal Diode - Bhunia , S.; Das, P. K.; Rakshit, S.; Manik, N. B. (Journal of Scientific Research, 2022)
The study on the semiconducting properties of herbal dye and various parameters of the herbal dye-based device is an important area of research in the coming days. In this work, we have measured the conductivity and Hall coefficient of turmeric dye in solid thin film form. Using the working principle of the Hall Effect, we have measured the Hall coefficient (HC) of this film. It is found that the curves of Hall voltage (VH) –Hall current (HC) and Hall voltage (VH) – Magnetic field (BH) are linear. The Hall coefficient has been estimated from these curves. The average value of the Hall coefficient (R) is 22.64 × 10-4 . The conductivity (σ) of the film is 1.5 10-10 m-1. We have estimated charge carrier density from this parameter, and its typical value is 2.8 23 m-3. We have also prepared a diode using this turmeric dye and extracted reverse saturation current, rectification ratio, ideality factor, series resistance, etc. It has been noticed that the diode exhibits high ideality factor and series resistance. The presence of traps is one of the main reasons for these high values. So, we have also measured the trapped energy of the device considering exponential trap distribution.